Legal Strength of Village Head Certificate As a Basis for Land Ownership Rights - Esau Djaha; Basuki Rekso Wibowo; Dedy Ardian Prasetyo (Pelopor Publikasi Akademika, 2025)
Law Number 5 of 1960 concerning the Basic Agrarian Law (UUPA) in Article 19 mandates the implementation of land registration with the aim of providing legal certainty and protection. The research method used is normative juridical with an analytical approach, with a descriptive analytical specification. Normatively (das-sollen), the provisions regulated in the legislation always state that the purpose of land registration is to achieve legal certainty through the issuance of certificates. Empirically (das-sein), the reality in practice shows that land conflicts are cross-sectoral issues, where each sector has its own rules that overlap with one another. This correlates with differences in perceptions and relations between the parties involved in the agrarian conflict itself. The research findings show that the court's decision in resolving land conflicts with evidence of Village Certificates / Land Certificates is as follows: In practice, it turns out that obtaining a certificate is not as easy as the ideal condition it should be. Constraints such as distance from the administrative center, untidy and overlapping records, difficulties in field verification facilities, and various other obstacles make obtaining a certificate not a simple task. Village Certificates (SKD)/Land Certificates (SKT) are factually easier to obtain because they only require the authority of the village and records available at the village head's office. SKD/SKT is actually a supporting document and not a primary document, but in court, this document can serve as valid evidence of land ownership rights, replacing the primary certificate due to the significant role of the judge.